SEISMO-ELECTRIC PHENOMENA FROM GRANITE CRACK CONTAINING CRUDE OIL - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 2007)
Seismo-electric phenomena gained more attention from geophysicists over the last decade.The development of theoretical background and the success of laboratory experimentsas well as limited field applications give a lot of opportunities and hope as a meansfor providing exploration and production data. Seismo-electric effect accommodates anyphenomena which links seismic and electrical energy including seismic to electric conversionas well as electro kinetic in origin.Experiment has been conducted to prove that free ions can be considered to accumulateinside a granite crack containing crude oil which in turn can generate stream oscillatoryelectric current when a seismic wave hit the fracture. As a result, electric potential canbe detected at the mouth of the fracture which intersects the borehole. The environmentalnature of the mouth which is full of fluid facilitates the detection of high resolution seismoelectricsignal by simple electrodes which is made of metal.